A seasonal transition in biological carbon pump efficiency in the northern Scotia Sea, Southern Ocean. (April 2023) - Henson, Stephanie A.; Briggs, Nathan; Carvalho, Filipa; Manno, Clara; Mignot, Alexandre; Thomalla, Sandy
Abstract: The biological carbon pump (BCP) contributes to the oceanic CO2 sink by transferring particulate organic carbon (POC) into the deep ocean. The magnitude and efficiency of the BCP is likely to vary on timescales of days to seasons, however characterising this variability from shipboard observations is challenging. High resolution, sustained observations of primary production and particle fluxes by autonomous vehicles offer the potential to fill this knowledge gap. Here we present a 4 month, daily, 1 m vertical resolution glider dataset, collected in the high productivity bloom, downstream of South Georgia, Southern Ocean. The dataset reveals substantial temporal variability in primary production, POC flux and attenuation. During the pre-bloom peak phase we find high export efficiency, implying minimal heterotrophic POC consumption, i.e. productivity is decoupled from upper ocean remineralisation processes. As the bloom progresses from its peak through its declining phase, export flux decreases, but transfer efficiency within the upper 100 m of the mesopelagic increases. Conversely, transfer efficiency in the lower mesopelagic decreases in the post-bloom phase, implying that the flux attenuation processes operating in the upper and lower mesopelagic are effectively decoupled. This finding underscores an important limitation of using a single parameter, such as Martin's 'b', to characterise POC flux attenuation in a given location or season. Frequent pulses of export flux are observed throughout the deployment, indicating decoupling between primary production and the processes driving export of material from the upper ocean. The mechanisms underlying the observed seasonal changes in BCP magnitude and efficiency are unclear, as temperature and oxygen concentration changed minimally, although the nature of the sinking particles changed substantially as the bloom progressed. Our results highlight the difficulty of capturing temporal variability and episodic flux events with traditional shipboard observations, which affects our conceptual understanding of the BCP. The increasing use of autonomous vehicles to observe particle fluxes will be essential to characterising the temporal variability in magnitude and functioning of the BCP.